2017
DOI: 10.1093/treephys/tpx133
|View full text |Cite
|
Sign up to set email alerts
|

The role of arginine metabolic pathway during embryogenesis and germination in maritime pine (Pinus pinaster Ait.)

Abstract: Vegetative propagation through somatic embryogenesis is critical in conifer biotechnology towards multivarietal forestry that uses elite varieties to cope with environmental and socio-economic issues. An important and still sub-optimal process during in vitro maturation of somatic embryos (SE) is the biosynthesis and deposition of storage proteins, which are rich in amino acids with high nitrogen (N) content, such as arginine. Mobilization of these N-rich proteins is essential for the germination and productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 60 publications
2
29
0
Order By: Relevance
“…In some circumstances, protein profiles can be markers of the N status of the sample . In the present experience using tomato plants, there are no significant differences, only minor changes, such as the absence of some proteins lower than 37 kDa in the N‐ roots compared with that in N+ roots (Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 64%
“…In some circumstances, protein profiles can be markers of the N status of the sample . In the present experience using tomato plants, there are no significant differences, only minor changes, such as the absence of some proteins lower than 37 kDa in the N‐ roots compared with that in N+ roots (Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 64%
“…L-arginine is synthesized from L-glutamate and is an amino acid with an important role as an N reserve in pine. This amino acid is very abundant in storage proteins and is an important sink for assimilated N surplus [20,36]. Additionally, the metabolite profile in the roots indicates that the availability of C for metabolic processes was reduced in nitrate-fed seedlings ( Figure 6, Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…However, after the completion of the Arabidopsis genome sequence [ 14 ], it was found that genes encoding most arginine biosynthetic enzymes contain a presequence for chloroplast targeting [ 15 ]. Recent localization studies have confirmed these genomic data and have provided strong evidence showing that the complete pathway is confined to plastids, including the enzymes of ornithine pathway and those involved in the biosynthesis of arginine from ornithine, OTC, ASSY and ASL [ 4 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 96%
“…The biosynthesis of arginine can be divided into two pathways: the conversion of glutamate into ornithine and the synthesis of arginine from ornithine through the sequential action of the enzymes ornithine transcarbamylase (OTC), argininosuccinate synthetase (ASSY) and argininosuccinate lyase (ASL) [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation